Water, water, everywhere? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Alternative Irrigation. The Promise of Runoff Agriculture CJ Barrow, Earthscan, 1999. 240 pp. ISBN 1 85383 496 3 GBP 15.95 E 25.40 Earthscan Publications Ltd 120 Pentonville Road London, N1 9JN, UK Fax: +44 20 7278 1142 Email: earthinfo@ear